Regeneration of Malaysian Indica Rice (Oryza sativa) Variety Mr232 via Optimised Somatic Embryogenesis System - Zaliha W.S; Sreeramanan Subramaniam, Zuraida Abdul Rahman, Suri Roowi, Wan (Journal of Phytology, 2010)
In vitro studies of indica rice variety MR232 via somatic embryogenesis system was established by using mature seeds. By manipulating various plant growth regulators, the optimum medium was obtained by using MS medium containing 5 mg/L NAA (a-naphthaleneacetic acid) and 1 mg/L 2, 4-D (2,4-dichlorophenoxyacetic acid) without browning effect. This treatment showed higher percentage of callus induction and frequency of embryogenesis at the range of 91-97%, which was further, confirmed with the histology studies. The highest whitish somatic embryos frequency (87%) was initiated by incubating embryogenic calli on media containing 10 mg/L ABA and 9 mg/L gelrite agar for 4 weeks. However, the numbers of regenerated plant on medium containing NAA and that was previously pre-treated with 10 mg/L ABA, 9 mg/L gelrite agar and incubation at 8 weeks was the best treatment for shoots induction with 10 plantlets per 3 gm of somatic embryos.